PENGELOLAAN LINGKUNGAN PADA AREA REKLAMASI PT INSANI BARAPERKASA KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR: Environmental Management in the Reclamation Area of PT Insani Baraperkasa Kutai Kartanegara Regency East Kalimantan Province - Novita Arumsari; Madina Dwi Panuntun; Auliya Rahmatul Ummah (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
East Kalimantan as one of the largest coal producing regions in Indonesia faces significant challenges in post mining environmental management. Intensive coal mining activities can cause environmental damage, necessitating reclamation efforts to restore the disturbed ecosystem functions. This study aims to identify and analyze the environmental management practices implemented in the reclamation area of PT Insani Baraperkasa (PT IBP) in Kutai Kartanegara Regency, East Kalimantan. Reclamation activities are crucial for restoring the quality of soil and ecosystems that have been impacted. The study uses qualitative methods with field observations and interviews. The results show that PT IBP has implemented reclamation measures, including the use of bank soil, organic fertilizer, and the planting of pioneer and local plants to improve soil and ecosystem quality. Vegetation growth monitoring is conducted periodically to ensure the success of the reclamation. PT IBP's reclamation practices demonstrate the company's commitment to improving the condition of post-mining land and supporting environmental sustainability.